Assessment of the reliability of vanadium-redox flow batteries - Reichelt, Florian; Müller, Karsten (Engineering Reports, 2020)
Redox flow batteries are an interesting energy storage technology because they allow separate scaling of power and capacity. For their utilization on large scale, it is crucial to ensure reliable operation. Failure modes of elements of the system have been evaluated, both, regarding failure rate and severity of the different failures. As the main failure mode directly linked to a specific component of the redox flow technology, degradation of the membrane due to oxidation by vanadium ions has been identified. However, it is demonstrated that reliability is not solely determined by the specific electrochemistry of the technology. A huge share of the overall failure rate is due to mechanical components such as pumps, valves, and sealing. Based on the findings it can be recommended to design the systems with a certain redundancy regarding cells and pumps but avoid excessive redundancy. This is crucial not only because of high CAPEX of redundant systems, but also because of the increased complexity with more valves and connections required for integrating redundant units.
CRIS-Team WoS Importer:2021-08-13